Learning to reason: the factorial survey as a teaching tool in social work education. Issue 3 (1st September 2016) - Wallander, Lisa; Molander, Anders
Abstract: This article proceeds from the notion that the ability to reason well – i.e. to try to find justified answers to questions such as 'what is the case?' and 'what ought to be done?' – constitutes an essential professional skill, which can be acquired and advanced in professional education. Accordingly, drawing on the much-used argument model developed by the philosopher Stephen Toulmin, we present a conceptual model for professional reasoning and propose an innovative tool for exercising reasoning in professional education. The tool involves the sociologist Peter Rossi's factorial survey method, which is based on the use of experimentally constructed fictive descriptions (vignettes). By having students make judgements of a large number of short vignettes ( N  = 96) and conducting statistical analyses separately for each individual, we construct judgement profiles displaying the causal predictors of each student's judgements. These profiles are subsequently employed in reflective discussions and for constructing arguments in accordance with the Toulmin model. By focussing in detail on the structure and contents of the arguments underlying each student's judgements, this teaching tool provides a number of advantages. For example, it can be used for making arguments relying on less reliable knowledge sources more transparent and thus open to scrutiny. Further, due to its experimental features, the tool makes it possible to analyse results of both reflective and intuitive thinking. Furthermore, it offers a way of encouraging the students to deal in an analytic and deliberate manner with the potential cognitive errors resulting from intuitive thinking, such as stereotyping.